Effectiveness of Solution-focused Brief ‎Therapy and Adlerian Therapy in Reducing ‎Academic Procrastination and Enhancing ‎Optimism‏ ‏among High-school Female ‎Students - Alguzo, Naela; Jaradat, Abdul-Kareem (Jordan Journal of Educational Sciences, 2021)
The present study aimed to compare the effectiveness of solution-focused brief therapy (SFBT) and Adlerian therapy (AT) in reducing academic procrastination and enhancing optimism among high-school female students. The sample of the study consisted of 60 female students in the tenth and eleventh grades at a public school in Irbid governorate, Jordan. In this study, an academic procrastination scale consisting of 15 items and an optimism scale consisting of 8 items were used. The participants were selected based on their high scores on the academic procrastination scale and low scores on the optimism scale. They were randomly assigned to three equal groups; two experimental groups and one control group. One of the experimental groups received a program of SFBT, the other experimental group received a program of AT and the control group didn't receive any treatment. The post-test results showed that SFBT and AT were significantly more effective in reducing academic procrastination and enhancing optimism than no treatment. Additionally, SFBT was significantly more effective in reducing academic procrastination than AT. Based on the results of the present study, it was recommended that school counselors should be trained to use the SFBT techniques as well as the AT for helping school students cope with their academic and personal problems